THE ROMANESQUE REVERSE IN SAMUEL BECKETT’S ANTI-NOVELS - Fuat BOYACIOĞLU (Fırat University, 2019)
In the XXth century, the reaction is seen against the forms and conventions of the past in all literary fields. Thus, a new literary turning is seen in the field of literature as in the fields of other branches of science after two great world wars which have caused anxiety, anguish and distress in the human tired of living under the difficult conditions to bear. These reactions are appeared in the novels and theatral works. The anti-novel and the anti-theater are the productions of these reactions againts the past. Somenovelists, theater players, dramaturges, poets etc seek to shake the readers or spectators by putting them directly in front of unusual situations and different writting forms. In this respect, there is a relative or a common intention between the anti-novel and anti-theater who aim to disturb the public, to get him out of his lazy habits and make him think. Samuel Beckett wrote both anti- novels and anti- theaters. His Waiting for Godot written both in french and in english is one of the most beautiful examples of the absurd theater or anti-theater. This theater piece is both absurd theater and a theater of derision. In this study we tried to expose how Samuel Beckett puts in problematic the traditional novel and its classique elements such as story, character, time and space by giving examples of his novels anti romaneques.